2021
DOI: 10.3390/bios11110414
|View full text |Cite
|
Sign up to set email alerts
|

Functional Ionic Liquids Decorated Carbon Hybrid Nanomaterials for the Electrochemical Biosensors

Abstract: Ionic liquids are gaining high attention due to their extremely unique physiochemical properties and are being utilized in numerous applications in the field of electrochemistry and bio-nanotechnology. The excellent ionic conductivity and the wide electrochemical window open a new avenue in the construction of electrochemical devices. On the other hand, carbon nanomaterials, such as graphene (GR), graphene oxide (GO), carbon dots (CDs), and carbon nanotubes (CNTs), are highly utilized in electrochemical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 169 publications
(179 reference statements)
0
12
0
Order By: Relevance
“…Figure 12 illustrates the finding and usage of carbon nanomaterials (CNMs) and ILs and their yearly publications, showing that ILs and CNMs are currently becoming researchable fields. [ 98 ]…”
Section: Applications Of Ils‐based Polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 12 illustrates the finding and usage of carbon nanomaterials (CNMs) and ILs and their yearly publications, showing that ILs and CNMs are currently becoming researchable fields. [ 98 ]…”
Section: Applications Of Ils‐based Polymer Compositesmentioning
confidence: 99%
“…The bar chart shows the numeral of articles every year from 2010 to 2021. Reproduced with permission [98]. Copyright 2021, MDPI.…”
mentioning
confidence: 99%
“…The low toxicity, biocompatibility, and adhesive property of ILs favor the immobilization of antibodies without any adverse effects. Various results suggested that the combination of ILs and GO turns to superior material to the unaided GO or ILs. However, to further improve the properties of the GO-IL nanocomposite, gold nanoparticles (AuNPs) were combined with the GO-IL nanocomposite, which is highly conductive and biocompatible and has a large surface area that significantly enhances the conductivity of the nanocomposite and effective surface area. , The resultant GO-IL-AuNP hybrid nanocomposites have high potential in immunosensor application. Hence, they are widely utilized for the fabrication of highly sensitive and specific electrochemical immunosensors for the detection of cancerous and other biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IL remarkably converts into a more electroconductive nanocomposite when it is incorporated with the nanomaterials. 31,32 Shang et al reported an electrochemiluminescence immunosensor of a hybrid nanocomposite of ionic liquid-functionalized graphene-platinum and gold nanoparticles (AuNPs) capped MXene for immunosensing of CEA. 33 Very recently, Ranjan et al detected the CD44 BC biomarker up to the femto molar concentration using an electrochemical immunosensor based on graphene oxide-ionic liquid-gold nanoparticles (GO-IL-AuNPs).…”
Section: Introductionmentioning
confidence: 99%
“…IL is a room-temperature liquid (melting point <100 °C) of various combinations of organic cations and inorganic anions that possess high electroconductivity and biocompatibility. , Additionally, the high thermal stability, broad electrochemical window, high viscosity, adhesive property, low toxicity, and easy functionalization with nanomaterials make them a promising candidate for electrochemical immunosensing applications. Furthermore, IL remarkably converts into a more electroconductive nanocomposite when it is incorporated with the nanomaterials. , Shang et al reported an electrochemiluminescence immunosensor of a hybrid nanocomposite of ionic liquid-functionalized graphene-platinum and gold nanoparticles (AuNPs) capped MXene for immunosensing of CEA . Very recently, Ranjan et al detected the CD44 BC biomarker up to the femto molar concentration using an electrochemical immunosensor based on graphene oxide-ionic liquid-gold nanoparticles (GO-IL-AuNPs) .…”
Section: Introductionmentioning
confidence: 99%